ChemInform Abstract: A Three‐Way Switchable Process for Suzuki Cross‐Coupling, Hydrodehalogenation, or an Assisted Tandem Hydrodehalogenation and Suzuki Cross‐Coupling Sequence. Issue 16 (22nd April 2014) - Sandtorv, Alexander H.; Bjoersvik, Hans‐Rene
Abstract The Suzuki reaction of 4, 5‐iodoimidazole is thoroughly investigated.